Reflections on a Physician Assistant Entrance Exam: Does the Profession Need One?. Issue 1 (March 2021) - VanderMeulen, Stephane; Hills, Karen; Snyder, Jennifer A.; Kohlhepp, William; Alexander, Lisa Mustone; Bowser, Jonathan; Lane, Steven
Abstract: Standardized entrance exams are used in many health professions as one way to objectively measure knowledge and facilitate comparisons across student groups. The physician assistant (PA) profession has historically not employed a profession-specific entrance exam, and the idea was never seriously explored until the Physician Assistant College Admissions Test was developed recently by a commercial assessment publisher, with field testing in some volunteer programs in 2018 and the exam's first administration in May of 2020. The 2020 Physician Assistant Education Association Presidents Commission chose to investigate the issues raised by a consensus-derived, PA-specific entrance exam to stimulate more informed discussion on the efficacy of such an exam. While it may have the potential to enhance efficiency in PA admissions and reduce variability in admissions requirements, a PA entrance exam would also likely introduce new challenges, including increased costs, impact on the diversity of the applicant pool, and incongruence with an increasingly holistic admissions process. The biggest barrier would likely be the lack of current consensus on the knowledge, skills, and attributes that matriculants need to be successful in the program and in clinical practice. Development of a consensus-derived PA entrance exam would be a complex, expensive, and time-consuming endeavor, requiring considerable attention to technical issues of psychometric quality, process transparency, and legal defensibility. Changes being made to health professions admissions practices due to the COVID-19 pandemic, including the dropping of test scores as a requirement by some institutions, may make some of the issues raised in this paper more timely than ever.